IEEE 2013 Tencon - Spring 2013
DOI: 10.1109/tenconspring.2013.6584473
|View full text |Cite
|
Sign up to set email alerts
|

Frequency allocation with Artificial Neural Networks in cognitive radio system

Abstract: Cognitive radio is based on the thought of adaptive frequency allocation. It solves the problems of spectrum lack and spectrum inefficiency in current communication networks. In this paper we propose a solution using Artificial Neural Networks (ANNs) to replace a complicated frequency allocation system in the cognitive radio. The solution will make sure that the frequency allocation working well in an easier system and with less waste of resource. We present the analysis of multi-user with different weights an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…The ANN gets information from the neighboring neurons and gives an output depending on its weights and functions. Tan et al, (2013) found the cons of spectrum lack and inefficient in the communication networks and the by introducing new solutions using ANN by replacing the current frequency allocation system.…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…The ANN gets information from the neighboring neurons and gives an output depending on its weights and functions. Tan et al, (2013) found the cons of spectrum lack and inefficient in the communication networks and the by introducing new solutions using ANN by replacing the current frequency allocation system.…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…In this paper, the author used the Combination of Cognitive Radio and Back Propagation (BP) Artificial Neural Network (ANN) both together for the replacement of Complicated Frequency allocation, from the Simulation author comparing Back Propagation (BP) Artificial Neural Network (ANN) with the original Frequency Allocation which is able to give out the accurate simulation results which means that the BP ANN gave the solution of Complicated frequency allocation and by using this method we will get accurate results of frequency allocation which also increases the Quality of Service and reduces the interference [42].…”
Section: Machine Learning Models/techniques Proposed For Implementatimentioning
confidence: 99%
“…In [21], the authors introduces an artificial neural network based learning scheme for predicting data rate for specific radio configuration and used the algorithm for estimating the performance of data rate and throughput. In [22], the author the Combination of Cognitive Radio and Feed Forward Back Propagation both together for the replacement of Complicated Frequency allocation, from the Simulation author comparing Back Propagation (BP) Artificial Neural Network (ANN) with the original Frequency Allocation which is able to give out the accurate simulation results which means that the BP ANN gave the solution of Complicated frequency allocation and by using this method we will get accurate results of frequency allocation which also increases the Quality of Service and reduces the interference.…”
Section: Artificial Neural Network (Ann)mentioning
confidence: 99%